Bare mountaintops and thirsty cities: On California and its snowpack - RANDLE, Sayd (Institutional Knowledge at Singapore Management University, 2019)
Figuring how to represent the oncoming effects of climate change is a common challenge faced by whistleblowers and policymakers attempting to alert populations. Sayd Randle shows how the state of California is trying to mobilize the monitoring of snow in the Sierra Nevada as a harbinger of a durable state of drought in the coastal cities.